Heritability and Correlations Among Fodder Yield Components in a Pasture Grass, Dichanthium annulatum - Yadav, M. S.; Mehra, K. L.; Magoon, M. L. (Indian Forester, 1976)
Haritability, genetic advance and simple correlations among six characters were analysed in eighteen genetic stocks of the pasture grass, D.annulatum Stapf. The differences among the varietal means were significant for all characters. The phenotypic and genotypic coefficients of variability were moderate for some characters and low for the others. The heritability and genetic advance (in percent of the mean) of the characters studied ranged from 27.9 to 90.5% and 13.2% to 87%, respestively. Leaf number, tiller number and fodder yield showed comparatively higher heritabilities and genetic advances as compared to those of the other characters, indicating that straight selection is likely to lmprove them. Among the character correlations studied, only the tiller number was significantly and positively correlated with the fodder yield at the phenotypic level. The leaf number showed significant and positive phenotypic correlation with the culm girth and node number It was, therefore, suggested that while the breeders should aim at selecting highly tillering plants, the quality of the herbage vis-a-vis its leafiness should not be lost sight of.